Place brand communication as aspirational talk-further exploring the constitutive model of communication (Communication & Society, 2018)
This paper introduces the concept of aspirational talk to examine the constitutive features of place brand communication. Aspirational talk builds on a performative view of communication and is characterised by a gap between future-oriented visionary talk and concrete action. The study explores place brand communication as aspirational talk through a qualitative case study of how place branding is used to drive changed in two Swedish cities. Two ideological different aspirations are identified and contrasted. It is argued that aspirational talk helps us to further understand the gap between the political visions and ideals that underpin place brand communication and residents’ everyday life in the city.